Effect of angiotensin‐converting enzyme inhibition on cardiovascular adaptation to exercise training - Tórur Sjúrðarson; Jacob Bejder; Andreas Breenfeldt Andersen; Thomas Bonne; Kasper Kyhl; Tóra Róin; Poula Patursson; Noomi Oddmarsdóttir Gregersen; May‐Britt Skoradal; Michael Schliemann; Malte Lindegaard; Pál Weihe; et al. (Physiological Reports, 2022)
Abstract Angiotensin‐converting enzyme (ACE) activity may be one determinant of adaptability to exercise training, but well‐controlled studies in humans without confounding conditions are lacking. Thus, the purpose of the present study was to investigate whether ACE inhibition affects cardiovascular adaptations to exercise training in healthy humans. Healthy participants of both genders (40 ± 7 years) completed a randomized, double‐blind, placebo‐controlled trial. Eight weeks of exercise training combined with placebo (PLA, n = 25) or ACE inhibitor (ACEi, n = 23) treatment was carried out. Before and after the intervention, cardiovascular characteristics were investigated. Mean arterial blood pressure was reduced (p < 0.001) by −5.5 [−8.4; −2.6] mmHg in ACEi, whereas the 0.7 [−2.0; 3.5] mmHg fluctuation in PLA was non‐significant. Maximal oxygen uptake increased (p < 0.001) irrespective of ACE inhibitor treatment by 13 [8; 17] % in ACEi and 13 [9; 17] % in PLA. In addition, skeletal muscle endurance increased (p < 0.001) to a similar extent in both groups, with magnitudes of 82 [55; 113] % in ACEi and 74 [48; 105] % in PLA. In contrast, left atrial volume decreased (p < 0.05) by −9 [−16; −2] % in ACEi, but increased (p < 0.01) by 14 [5; 23] % in PLA. Total hemoglobin mass was reduced (p < 0.01) by −3 [−6; −1] % in ACEi, while a non‐significant numeric increase of 2 [−0.4; 4] % existed in PLA. The lean mass remained constant in ACEi but increased (p < 0.001) by 3 [2; 4] % in PLA. In healthy middle‐aged adults, 8 weeks of high‐intensity exercise training increases maximal oxygen uptake and skeletal muscle endurance irrespective of ACE inhibitor treatment. However, ACE inhibitor treatment counteracts exercise training‐induced increases in lean mass and left atrial volume. ACE inhibitor treatment compromises total hemoglobin mass.